The Role of Locally-Generated Revenue in Mediating The Influence of Credit Distribution on Economic Growth in East Java - Purnomo, Okky; Kristijadi, Emanuel (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to test the role of locally-generated revenue in mediating the influence of credit distribution on economic growth in East Java. The research population was all cities and districts in East Java, and all of them were studied. The method used is the structural equation model and the Sobel Test to test its mediation role. Data from 38 cities and districts during 2018-2022 were processed using Eviews 12. The results of this study indicate that the distribution of working capital, investment and consumer credit has a positive and significant effect on economic growth in East Java. The distribution of working capital, investment and consumer credit does not have a significant influence on locally-generated revenue. Locally-generated revenue also does not have a significant influence on economic growth, so locally-generate revenue is also unable to mediate the positive influence of the credit distribution on economic growth in East Java.